Preliminary Analysis: Development of Higher Order Thinking Skills Problem on Stoichiometry Topic Using the Rasch Model - Abdullah Abdullah; Rasmiwetti Rasmiwetti; Ardiansyah Ardiansyah (Pendidikan Kimia Unimus, 2022)
This study is a part of the development study of stoichiometric HOTS problems. This study aimed to develop the stoichiometry Higher Order Thinking Skills (HOTS) test instrument. The stages of the study started with analyzing the material on the stoichiometry topic. The test consisted of 10 multiple-choice questions with 5 answer options. The instrument test was assessed by two chemistry education experts before being administered to 26 high school students in Pekanbaru city. The test results were analyzed with the Rasch Measurement Model (RMM) using the Win Step software. RMM was useful to investigate item validity, item and person reliability, and item-person map. All of these criteria were useful in improving the quality of the instrument based on Item Response Theory. The results showed that almost all items were valid, except for the Q16 items. Thus, these nine items could be used as higher-order thinking test instruments for a larger sample.